2019
DOI: 10.5430/ijfr.v10n6p159
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Green Performance in Manufacturing Industries

Abstract: The study aims to examine the factors that influence green performance in the manufacturing industry as it has become a burning topic in recent times.Structural Equation Modeling (SEM) has been used as a tool to analyze the data collected from different management levels of employees from the manufacturing industries in Bangladesh. The study shows that environmental performance (ENP) is the most significant factor affecting green performance (GP) in the manufacturing industry. Moreover, economic performance (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Earlier studies in the context of Bangladesh witnessed modest CSR disclosures and provided mostly employeerelated descriptive information that raised the question of data integrity (Rashid et al, 2019). Moreover, Azim et al (2009) also reported that only one-sixth of the publicly-traded companies in Bangladesh disclosed CSR issues voluntarily.…”
Section: Corporate Social Responsibility Disclosure Practices In Bangmentioning
confidence: 99%
“…Earlier studies in the context of Bangladesh witnessed modest CSR disclosures and provided mostly employeerelated descriptive information that raised the question of data integrity (Rashid et al, 2019). Moreover, Azim et al (2009) also reported that only one-sixth of the publicly-traded companies in Bangladesh disclosed CSR issues voluntarily.…”
Section: Corporate Social Responsibility Disclosure Practices In Bangmentioning
confidence: 99%
“…The term “social responsibility” originated in the 1950s and gained broad use in the 1970s (Shukair, 2015). Over the previous two decades, empirical research has started to establish the importance of CSR as a tool for business that benefits stakeholders (Rashid et al, 2019). We describe CSR in accordance with Aguinis's (2011) concept, which is situationally organizational activities and policies that include stakeholders' aspirations as well as the three pillars of financial, social, and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturing industry tends to generate more negative outcomes on the environment than the service industry, thus necessitating their adoption of sustainable business practices [12,29]. Some researchers identified factors like institutional pressure [30] and green practice [31] as influencing the sustainability performance of the manufacturing industries in Bangladesh. Earlier studies conducted in developed and emerging economies have demonstrated the influence of ESG principles on sustainable business performance.…”
Section: Of 23mentioning
confidence: 99%